Inovasi Pelayanan Rumah Sakit Bagi Penyintas COVID-19: Tinjauan Literatur - Selly Gloria Lengkong; Wahyu Sulistiadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Coronavirus Disease 2019 (COVID-19) is a disease that continues to be studied because of its rapid changes. The higher COVID-19 recovery rat, the higher the occurrence of follow-up events for patients after recovering from COVID-19. Hospitals as health care facilities have a role not only to ensure patient safety, but also to maintain the patients’ quality of life so that they can continue working after recovering from the illness. The COVID-19 pandemic which has caused a decrease in number of outpatients has forced hospitals to have creative innovations to increase the number of visits to keep their services running. This article uses a literature review method from two databases, PubMed and Google Scholar. Based on the literature found, there are several things that hospitals can do as innovations in their services during the COVID-19 pandemic, such as holding a Medical Check-up program for COVID-19 survivors and a post-COVID-19 Rehabilitation program that involves multidisciplinary care from various specialties, such as pulmonary, cardiac, neurological, medical rehabilitation, and psychiatry. To keep giving the best care a hospital can give to the patients while maintaining the quality of life of COVID-19 survivors, the hospital may consider making a Medical Check-up program and a Post-COVID-19 Rehabilitation program for COVID-19 survivors.